2021
DOI: 10.3389/fpubh.2021.648196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Triclosan Exposure on Neonatal Birth Weight and Children Triclosan Exposure on Children's BMI: A Meta-Analysis

Abstract: Background: Triclosan (TCS) is an environmental chemical with endocrine disrupting effects and can enter the body through the skin or oral mucosa. Human data about the effect of TCS exposure during pregnancy on neonatal birth weight and TCS exposure during childhood on children's growth are scarce.Objectives: To investigate the association between maternal urinary TCS level and neonatal birth weight, as well as children's urinary TCS level and children's body mass index (BMI).Methods: A systematic literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Childhood triclosan exposure did not affect BMI [655] in three studies. An NHANES crosssectional human study showed an association between triclosan exposure and BMI [668]. Another cross-sectional study showed triclosan and triclocarban were associated with an increased risk of childhood obesity [669].…”
Section: Triclosanmentioning
confidence: 99%
“…Childhood triclosan exposure did not affect BMI [655] in three studies. An NHANES crosssectional human study showed an association between triclosan exposure and BMI [668]. Another cross-sectional study showed triclosan and triclocarban were associated with an increased risk of childhood obesity [669].…”
Section: Triclosanmentioning
confidence: 99%
“…Heterogeneity among studies was evaluated through Q statistic. Given that heterogeneity was nonnegligible between only 12 studies included in this meta-analysis, a random-effects model was applied to calculate the combined effect value compared with fixed effects models according to our previous study [ 17 ]. Further, a one-by-one elimination method was used to perform sensitivity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In children of aggressive periodontitis parents, a TRC toothpaste was demonstrated to be efficient in the management of the periodontal condition through the reduction of bleeding on probing, pocket depth, salivary Aggregatibacter actinomycetemcomitans ( A. actinomycetemcomitans ) and inflammatory markers [ 129 ]. This compound inhibits the subgingival biofilm formation and the overnight plaque [ 130 , 131 ], but its use has been controversial due to possible associations with low neonatal birth weight [ 132 , 133 ].…”
Section: Oral Antiseptics and Oral Conditionsmentioning
confidence: 99%